Development of an Algorithm and Software System for Facing Panels Accounting on Production Lines - Ivanov, Yurii; Bilous, Petro; Botvinnikov, Viacheslav; Holovatyi, Maksym (Видавництво Львівської політехніки, 2023)
This paper aims to develop and implement an algorithm and an automated software system for the automatic accounting process of external facing panels during transportation on line conveyors. The method described in this paper is designed to simplify the process of production and accounting of wall-facing panels. This method can also serve as a model for implementing other manufacturers. The developed algorithm consists of the following steps: obtaining a video stream in real-time or from a file and its targeted processing and determining the number of moving objects of interest. The software accounting system created based on the developed algorithm analyzes the video data and stores all the necessary results and settings in the database. The software system can adapt to the accounting requirements of other types of similar products in other areas.
Keywords: Algorithm; computer vision; moving object; production line; video stream